Diagnostic performance of midupper arm circumference for detecting severe wasting among infants aged 1–6 months in Ethiopia. Issue 1 (12th November 2020) - Jima, Beshada R; Hassen, Hamid Y; Getnet, Yalemwork; Bahwere, Paluku; Gebreyesus, Seifu H
ABSTRACT: Background: Midupper arm circumference (MUAC) is used as an independent diagnostic tool to detect wasting in children aged 6–59 mo. However, little is known about the diagnostic performance of MUAC for detecting wasting among infants aged 1–6 mo. Objective: The objective of this study was to evaluate the diagnostic performance of MUAC in detecting severe wasting in infants aged 1–6 mo. Methods: We conducted a facility-based cross-sectional study among 467 hospitalized infants aged 1–6 mo in Ethiopia. Severe wasting was defined as having a weight for length z score (WLZ) below the cutoff value of −3 SDs from the median as per the WHO 2006 child growth standards. Receiver operating characteristic (ROC) analysis along with the calibration test was used to test the discriminatory performance of MUAC. Furthermore, we calculated the sensitivity, specificity, positive predictive value, and negative predictive value for the proposed optimal cutoffs. Results: The median age, MUAC, and WLZ were 100 d (IQR: 69–145 d), 119 mm (IQR: 103–130 mm), and −1.27 (IQR: −2.66 to 0.34), respectively. The prevalence of severe and moderate wasting was n = 101 (21.6%) and n = 61 (13.0%), respectively. The MUAC area under the ROC curve accuracy level in identifying severe wasting was 0.86 (95% CI: 0.82, 0.89). The optimal MUAC cutoff of ≤112 mm yielded the highest Youden index of 0.61, with a sensitivity of 85.1% (95% CI: 76.7%, 91.4%) and a specificity of 76.0% (95% CI: 71.2%, 80.2%). Conclusions: A MUAC cutoff of ≤112 mm performed well in detecting severe wasting among infants aged 1–6 mo. Further research is needed to evaluate the performance of MUAC for detecting wasting at community level and for predicting mortality among infants aged <6 mo.